Scenario modeling for prediction of contaminant transport in Perth unconfined aquifer - Shukla, Chirayu S. (Curtin University, 2008)
Rapid development and growth of industrialization has brought immense enrichments in living standards of humans, however, improper planned development also brings along several environmental problems such as pollution of environment and excessive consumption of natural resources. Among all the others, uncontrolled utilization of water poses a severe threat to the coming generations. Past decades have witnessed water shortage in various countries of the world. Although about 80% of the earth’s surface is covered with water, around 97.2% of water is salty making it inappropriate for general usage. Among the rest of the 2.8%, which is present as fresh water on surface, a large proportion of it has been found to be severely polluted. The increasing demand of fresh water both for industrial and domestic usage adds great demand on the available groundwater. Moreover, the severe pollution of fresh water on the surface adds more stress on the available groundwater. In Australia, approximately 20% of water supply is from groundwater and in the case of Western Australia groundwater provides two thirds of its water supply needs. Thus, it is important to manage groundwater sources in Western Australia to achieve the optimum water utilization and maintain the water table and it is also essential to decide on an appropriate water budget. Groundwater flow modelling is an effective tool to get appropriate water distribution and, to examine effects from pumping on water levels and direction of groundwater flow paths, thereby helping in its proper management and utilization. Apart from monitoring the flow and utilization, groundwater flow modeling is also vital to keep the track of pollutant in the groundwater. Increasing surface pollution and landfill sites tend to pollute the groundwater due to leaching.The above mentioned aspects formed the basis of the present research. A groundwater flow model was developed in Visual MODFLOW Premium to study the effect of three different types of soil in and around Perth region. This study also shows the hypothetical contaminated site model for benzene, toluene, ethylbenzene and xylene (BTEX) transport in Perth Superficial unconfined aquifer which includes three major aquifer sediments namely Bassendean Sand, Safety Bay Sand and Tamala Limestone. Among the four different contaminants it was observed that benzene is able to migrate quickly as compared to the other contaminants due to its smaller distribution coefficient.This study also explored the major soil parameters such as effect of sorption, effective porosity and hydraulic conductivity on contaminant plume configuration and contaminants concentration for the three types of aquifer sediments. A critical comparison of the behaviour of the three different types of soils was also conducted.Simulation results of sensitivity analysis have shown that sorption and hydraulic conductivity greatly affected the contaminant plume length and concentration of contaminants with much lesser effect shown by the effective porosity. The simulated results also showed that the movement of contaminant in Tamala Limestone is most rapid by comparing these three types of aquifer sediments together. Thus, it can be said that contaminated sites found in Tamala Limestone needs immediate remediation of contaminants to bring down the contaminants concentration in groundwater.In brief, the thesis explores the current groundwater scenario in and around Perth region. Based on the information a hypothetical scenario simulation has critically analyzed the various parameters affecting the water and contaminant flow for the various soil parameters. The study is considered as a building block for further research on developing a remediation technique for groundwater contaminant treatment.